Application of the Structure Equation Model: Impacts of Socio-economic Changes on Poverty Reduction in Vietnam's Ethnic Minority Region - Ha, Nguyen Thi Vinh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
In 2018, ethnic minority region of Vietnam has the rate of poor and near-poor households 3.5 times higher than the national average. There are many studies that have pointed out the causes of high poverty in ethnic minority areas and proposed policies to reduce poverty. However, poverty among ethnic minority groups remains an increasing and prolonged challenge. This article applies the structural equation model to consider impacts of socio-economic changes on poverty reduction in ethnic minority areas in Vietnam over the past 5 years, to provide recommendations for poverty reduction policies for ethnic minorities. Research results show that in addition to improving the quality of education, strengthening management and improving the quality of cultural activities, focusing on improving the spiritual significance of cultural activities - festivals - movements and promotion of ethnic minority identity can be the key to poverty reduction in these regions.